Development of the QR Code Frame Processing Method for Sorting Conveyor Lines - Nevliudov, I. Sh.; Yevsieiev, V.; Klymenko, O. (Черкаського національного університету імені Богдана Хмельницького, 2023)
QR codes are one of the most popular ways to mark goods and identify them on conveyor sorting lines. However, on mixed conveyor lines, where there may be different types of products with different types of packaging, there are problems with reading QR codes. One of the main problems is that mixed lines can have uneven lighting and different scanning angles, which can distort the QR code and make it difficult to recognize.
Keywords: conveyor sorting lines; QR codes